The ideological vision in Shahid al-Halfi's novel The Turban Thief (Journal of the College of Basic Education, 2023)
The plot of the novel ((The Turban Thief)) is based on a system of beliefs based on the contradiction between the sacred and the profane, the analyzed and the forbidden, the common and the abnormal. Not as an aesthetically influential vector in the recipient, but as an influential vector with an intellectual influence on him, to transfer from his conviction - the recipient - from an ideological focus to another ideological focus that is the objective of the correct narrator of the novel.